PENERAPAN METODE PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG NILAI-NILAI PANCASILA DI KELAS V SD - nurfaisah, andi; Latri, Latri; Cahyanianugrah, Nur (Universitas Negeri Makassar, 2025)
This research aims to describe the implementation of the Role Playing learning method to improve students' understanding of Pancasila values. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The subjects of this research were fifth-grade students at SD Inpres Malengkeri Bertingkat 1 Kota Makassar. The research findings show that the application of the Role Playing learning method in Pancasila education subjects can increase students' understanding of Pancasila values. This is indicated by the increase in student activity during the learning process and the improvement of their understanding as seen from the results of the final evaluation